Usage of e-book among university community - Komara, Seregbe; Wan Mamat, Wan Ali; Abu Bakar, Ahmad Bakeri (IIUM Press, 2011)
All these while, the concept of a book is that it is printed on paper, bound and portable. With the advent of computer technology and internet, a new form of book has developed, known as e-book. This is a trendy on the perception usage of e-book among selected group students in Malaysia and overseas.